Retrato da mudança na transição dos CNO para os CQEP – desafios da descontinuidade - Silva, Géraldine Pereira da; Ferreira, Maria Elisete Martins (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2017)
In the context of adult education, there were significant changes in the transition from the New Opportunities Centers (CNO) to the Centers for Qualification and Vocational Education (CQEP). The New Opportunities Initiative was considered an investment in Adult Education in Portugal, whereas the transition to CQEPs triggered a paradigm shift. In order to portray the perception that the CNO teams had in the transition process and organizational measures that took place between the CNOs and the CQEPs, a questionnaire was applied to the former CNO workers. The results showed that only 17% of respondents were admitted to a CQEP; the respondents holding a master’s degree were statistically the least integrated into a CQEP and those who were the least to believe in joining a CQEP, when compared with respondents with a lower level of qualifications; Former CNO workers were integrated in greater numbers in the Lisbon and Vale do Tejo region, and in smaller numbers in the Alentejo and Algarve region. Regarding the organizational practices in the transition process between the CNOs and the CQEPs, respondents stated that there was an absence of communication actions explaining the closure of the CNOs to the workers; the absence of requests for cooperation in the transition process of these two structures; the absence of information about a possible renewal of their contract for a CQEP and the failure to meet the deadlines set by ANQEP for the creation of the CQEP. Finally, it is noted that regardless of the integration of former CNO workers into a CQEP, most respondents did not agree on how the transition process between these two structures took place.